Perceptions of Pre-Service Teachers on Ethical Teacher and Professional Ethics Course - Süleyman Karataş; Mustafa Caner; R. Burak Kahyaoğlu; Sertaç Kâhya (Anı Publishing, 2019)
The purpose of the present study is to figure out the perceptions of pre-service teachers on the characteristics of ethical teacher and feasibility of Professional Ethics course that offered in a teacher certificate program. The study adopted an exploratory qualitative research design to explore the perceptions of the participants in depth. The participants of the study were 15 volunteer pre-service teachers who were selected with the convenience sampling technique. The data were gathered through semi structured one-to-one interviews and descriptively analyzed by means of content analysis technique. The analysis of the data revealed that participants perceived the teachers as ethical when they maintain professional relationships and do not discriminate students, demonstrate respect for diversity, maintain fairness and promote equality, act with honesty, integrity and fairness, take responsibility for maintaining the quality of their professional practice, maintain an up to date knowledge, work in a collegiate and cooperative manner with colleagues and other professionals and act obedient to law and regulations. Additionally, findings revealed that professional ethic course enable participants to gain awareness on ethical codes of teaching profession, able to identify ethical and unethical behaviors as well as increase their willingness to act in line with the codes of teaching professional ethics.